2005
DOI: 10.1542/peds.2004-1678
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Fabry Disease

Abstract: ABSTRACT. Background. Fabry disease is an underdiagnosed, treatable, X-linked, multisystem disorder.Objectives. To test the hypothesis that quality of life and sweating are decreased among pediatric patients with Fabry disease, compared with control subjects, and to provide quantitative natural history data and novel clinical end points for therapeutic trials.Design. Prospective, cross-sectional, observational study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
2
12

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 182 publications
(150 citation statements)
references
References 45 publications
8
128
2
12
Order By: Relevance
“…2,3 Another study compared HRQoL of boys with Fabry disease with controls. 17 Baehner et al 18 These studies comparing HRQoL between study subjects and control populations found statistically significant differences in HRQoL domains. Our study also found significant differences between controls and study subjects and is the largest study to date that compares HRQoL of heterozygous women to controls and chronic disease populations.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Another study compared HRQoL of boys with Fabry disease with controls. 17 Baehner et al 18 These studies comparing HRQoL between study subjects and control populations found statistically significant differences in HRQoL domains. Our study also found significant differences between controls and study subjects and is the largest study to date that compares HRQoL of heterozygous women to controls and chronic disease populations.…”
Section: Discussionmentioning
confidence: 99%
“…It is elevated in most patients when measured in a random sample of whole urine or urine deposited on a filter paper (Whatman 903) (3,6,7). Urine levels are highest in patients with null mutations and no residual enzyme activity and lower in female heterozygotes and patients with significant residual ␣-galactosidase A activity (6,8,9). When measured in random samples of whole urine, Gb 3 may even be normal in some of these patients and in female heterozygotes (6).…”
Section: What Do We Know?mentioning
confidence: 99%
“…This causes accumulation of glycosphingolipids, particularly globotriaosylceramide (Gb3) in most cell types [2]. Clinical onset of the disease typically occurs during childhood or adolescence with recurrent episodes of severe acroparethesias associated with a small-fiber neuropathy [3], characteristic cutaneous lesions known as angiokeratomas and a distinctive, but asymptomatic, corneal dystrophy [3]. Vital organs are affected with increasing age by a systemic vasculopathy that is associated with progressive cerebrovascular, cardiac or renal complications and early death [4].…”
Section: Introductionmentioning
confidence: 99%